La posición de Unamuno hacia la gramática, el latín y el griego - Maroco dos Santos, Emanuel José (2017)
Unamuno was a thinker committed to the educational reality of Spain in the late nineteenth and early twentieth centuries. Among his pedagogical concerns, we highlight his reflections on grammar, Latin and Greek. This study will attempt to cast some light on the leitmotiv of Unamuno’s criticism of the way these subjects were taught in his historical period, so as to clarify the theoretical scope of his educational proposals.